“Claim – Support – Question” Routine to Foster Coherence Within Interactive Oral Communication Among EFL Students (2018)
This article reports on the results of an action research study that aimed to determine the effect of a thinking routine in the development of coherence in speaking interactions. The study was carried out with two groups of second year business students in an English as a foreign language programt a university in southern Chile. A mixed methods approach was used to collect data before and after the intervention through questionnaires and pre- and post-tests. The findings suggest that the impact of the application of the routine was significant in promoting the speaking competence, especially in developing coherence within interactive communication.